1990
DOI: 10.1111/j.1469-8137.1990.tb00459.x
|View full text |Cite
|
Sign up to set email alerts
|

Recovery of kiwifruit vines from transient waterlogging of the root system

Abstract: SUMMARYThe extent to which kiwifruit vines {Actinidia deliciosa var. deliciosa) recovered from transient waterlogging of the root system was determined under controlled conditions. Vines were waterlogged for periods varying from 1 to 7 days. The effects of decreasing concentrations of oxygen in the root zone on growth of the vine were rapid with substantial reductions occurring after being exposed to oxygen concentrations in the surrounding water of less than 0-125 mmol 1"^ for as little as 1 day. There was no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
31
0
1

Year Published

1991
1991
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(35 citation statements)
references
References 25 publications
3
31
0
1
Order By: Relevance
“…Vigna unguiculata, Atkins et al, 1984), suggesting that they may be common in legume nodules. It is further possible that they are a device used in other plant tissues, for example, kiwi fruit {Actinidia deliciosa) roots, where Smith et al (1990) showed that an electron-dense intercelluar material normally present in unstressed roots was lost when they were waterlogged.…”
Section: Discussionmentioning
confidence: 99%
“…Vigna unguiculata, Atkins et al, 1984), suggesting that they may be common in legume nodules. It is further possible that they are a device used in other plant tissues, for example, kiwi fruit {Actinidia deliciosa) roots, where Smith et al (1990) showed that an electron-dense intercelluar material normally present in unstressed roots was lost when they were waterlogged.…”
Section: Discussionmentioning
confidence: 99%
“…One of the major anatomical effects of hypoxia occurs at the root level. Some studies have reported hypertrophic lenticel formation (Jones and Sharitz, 1990;Shimamura et al, 2010), adventitious root development, and parenchymal tissue changes (Aloni and Rosenshtein, 1982;McNamara and Mitchell, 1989;Smith et al, 1990). Several types of tropical and subtropical fruit trees show anatomical or morphological adaptations to flooding stress, such as the development of hypertrophied stem lenticels, adventitious rooting or the formation of porous aerenchyma tissue (Schaffer et al, 2006).…”
Section: Waterlogging Causes Anatomical Physiological and Molecular mentioning
confidence: 99%
“…The dynamics of root growth and the ability of trees to recover from transient inundations are significant in evaluating short-term effects of waterlogging (Smith et al, 1990). Species reduce their growth under anoxic conditions, but in contrast to sensitive species, tolerant species can resume growth rapidly once aeration has been restored.…”
Section: Transient Soil Waterlogging and Selection Of Tolerant Rootstmentioning
confidence: 99%